Caught between cultures: case study of an "out of school" ethnic minority student in Hong Kong - Bhowmik, Miron Kumar; Kennedy, Kerry J. (Asia Pacific journal of education, 2017)
This paper reports a case study on Maneesha Rai, a Nepalese girl living in Hong Kong and an "out of school" student. Based on in-depth interviews, a case was constructed of her previous school days and current "out of school" days. These provided a vivid picture of her life and several themes were created using schema analysis that help explain the reasons for her "dropping out" of school after Form Five. It has been common to attribute school failure for ethnic minority students in Hong Kong to problems with Chinese language education. Yet Maneesha's case study shows that her experience of failure in other subjects such as Mathematics and Science contributed to her lack of successful schooling. Maneesha's school failure was more than simply a consequence of academic failure. Rather, there were many other interrelated factors such as peer and community factors, dropout history in the family, racism, differences in schooling culture found that contributed to her school failure. In addition, Maneesha, like many of her ethnic minority friends, enjoyed the freedom afforded her in Hong Kong, but it seemed such freedom also meant inadequate attention from her teachers.